2021
DOI: 10.1097/md.0000000000023982
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors for acute respiratory distress syndrome in patients with severe acute pancreatitis

Abstract: Acute respiratory distress syndrome (ARDS) is very common in patients with severe acute pancreatitis (SAP), the early interventions are essential to the prognosis of SAP patients. We aimed to evaluate the risk factors for ARDS in SAP patients, to provide insights into the management of SAP. SAP patients treated in our hospital from June 1, 2018 to May 31, 2020 were included. The characteristics and lab test results were collected and compared, and we conducted the logistic regression analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
(20 reference statements)
3
13
0
Order By: Relevance
“…Overall, in this study 78 (32.5%) patients died during hospitalization, while in literature mortality rates as high as 30% [17]. The main cause of early death in AP patients is ARDS, 60% of our patients died in first 6 days of hospitalization mostly because of pulmonary complication [18]. In our study, according to the similarities between these two interleukins, their behavior in severe forms of acute pancreatitis is practically identical.…”
Section: Disscusionsupporting
confidence: 56%
“…Overall, in this study 78 (32.5%) patients died during hospitalization, while in literature mortality rates as high as 30% [17]. The main cause of early death in AP patients is ARDS, 60% of our patients died in first 6 days of hospitalization mostly because of pulmonary complication [18]. In our study, according to the similarities between these two interleukins, their behavior in severe forms of acute pancreatitis is practically identical.…”
Section: Disscusionsupporting
confidence: 56%
“…This is in accordance with data from other studies showing that hypercapnia is uncommon in COVID-19 patients, even in those admitted to ICU, 28 while hypoxia from early pulmonary involvement is the most common presentation feature. 4,29 NEWS-C, another modified version of NEWS, has recently been suggested for assessment of COVID-19 patients. 14 Age !65 years was added to NEWS-C as an independent risk factor based on recent reports in patients with influenza or other non-COVID infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…2 Typical COVID-19 patients present with fever, myalgia, fatigue, and dry cough. 3,4 Severe cases progress to severe dyspnoea and hypoxemia within one week after the onset of symptoms. 3À5 In hospitalized COVID-19 patients, the prevalence of hypoxemic respiratory failure is around 20%, and more than 25% of them may require intensive care treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, factors such as immature granulocyte percentage and C-response protein were identified to be linked with ARDS occurrence in AP. (43,44) However, no study has been done for performing a nomogram in order to predict the incidence of ARDS in AP.…”
Section: Discussionmentioning
confidence: 99%